Management of Advanced and Metastatic Prostate Cancer: A Need for a Sub-Saharan Guideline. (5th December 2019) - Cassell, Ayun; Yunusa, Bashir; Jalloh, Mohamed; Ndoye, Medina; Mbodji, Mouhamadou M.; Diallo, Abdourahmane; Kouka, Saint Charles; Labou, Issa; Niang, Lamine; Gueye, Serigne M.
Abstract : The estimated incidence rate of prostate cancer in Africa was 22.0/100, 000 in 2016. The International Agency for Research on Cancer (IARC) has cited prostate cancer as a growing health threat in Africa with approximated 28, 006 deaths in 2010 and estimated 57, 048 deaths in 2030. The exact incidence of advanced and metastatic prostate cancer is not known in sub-Saharan Africa. Hospital-based reports from the region have shown a rising trend with most patients presenting with advanced or metastatic disease. The management of advanced and metastatic prostate cancer is challenging. The available international guidelines may not be cost-effective for an African population. The most efficient approach in the region has been surgical castration by bilateral orchidectomy or pulpectomy. Medical androgen deprivation therapy is expensive and may not be available. Patients with metastatic castrate-resistant prostate cancer tend to be palliated due to the absence or cost of chemotherapy or second-line androgen deprivation therapy in most of Africa. A cost-effective guideline for developing nations to address the rising burden of advanced prostate cancer is warranted at this moment.